Anti-oxidative and Anti-microbial Activities of Purified MPN-1-1 from Persicaria nepalensis (Meisn.) Miyabe - Yang, Woong-Suk; Yang, Seung-Hoon; Lee, Jae-Yong; Jang, Seong-Ho; Kim, Cheorl-Ho; Hwang, Cher-Won (BENTHAM SCIENCE PUBL LTD, 2017)
Background: Persicaria is a genus of flowering plants generally used for traditional medicine and nutritional supplements in tropical and subtropical East Asian countries. Previous studies have shown that Persicaria extracts alleviate lipid peroxidation, hypertension, and inflammation. Objective: We investigated the anti-oxidative and anti-microbial effects of ethanol extracts of Persicaria nepalensis (Meisn.) Miyabe, and isolated and identified an active compound, MPN-1-1 from the ethanol extracts. Results: Anti-oxidative values, as indicated by the Oxygen Radical Absorbance Capacity (ORAC) assay, were enhanced by treatment with Persicaria nepalensis (Meisn.) Miyabe ethanol extracts, and bacterial growth was inhibited. The active compound (MPN-1-1), which was further isolated and purified from a Persicaria nepalensis (Meisn.) Miyabe ethanol extract by medium pressure liquid chromatography (MPLC), also had strong anti-oxidative and anti-microbial activity. H-1-NMR spectroscopy identified MPN-1-1 as a 1-ethenyl-4,8-dimethoxy-9H-pyrido(3,4-beta) indole compound, which is an alkaloid. Conclusion: Our results provide evidence that Persicaria nepalensis (Meisn.) Miyabe extract has strong physiological activity without any toxic effects, and furthermore, MPN-1-1 can be potentially utilized as a natural dietary supplement as well as an anti-oxidant.
Keywords: OXIDATIVE STRESS; DAMAGE